2013
DOI: 10.1002/cbic.201200728
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Isopenicillin N Synthase with Homologated Substrate Analogues δ‐(L‐α‐Aminoadipoyl)‐L‐homocysteinyl‐D‐Xaa Characterised by Protein Crystallography

Abstract: Isopenicillin N synthase (IPNS) converts the linear tripeptide δ-(L-α-aminoadipoyl)-L-cysteinyl-D-valine (ACV) into bicyclic isopenicillin N (IPN) in the central step in the biosynthesis of penicillin and cephalosporin antibiotics. Solution-phase incubation experiments have shown that IPNS turns over analogues with a diverse range of side chains in the third (valinyl) position of the substrate, but copes less well with changes in the second (cysteinyl) residue. IPNS thus converts the homologated tripeptides δ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…[46] Substrate analogue AhCV 34 readily binds to IPNS, although the increased flexibility of homocysteine causes multiple occupancy of the substrate (Figure 18A). [47] Crystallisation of the IPNSÀ FeÀ AhCV complex revealed that the additional methylene group introduces considerable flexibility when this analogue binds to IPNS. The IPNSÀ FeÀ AhCV complex shows multiple occupancy of the active-site region, including binding orientations in which the hC sulfur ligates to iron, [41,47] and conformations in which the hC side chain is oriented away from the metal, which is bound instead by the carbonyl oxygen of the hCÀ V amide bond (Figure 18A).…”
Section: Substrate Analogues With Altered Steric Profilesmentioning
confidence: 99%
See 3 more Smart Citations
“…[46] Substrate analogue AhCV 34 readily binds to IPNS, although the increased flexibility of homocysteine causes multiple occupancy of the substrate (Figure 18A). [47] Crystallisation of the IPNSÀ FeÀ AhCV complex revealed that the additional methylene group introduces considerable flexibility when this analogue binds to IPNS. The IPNSÀ FeÀ AhCV complex shows multiple occupancy of the active-site region, including binding orientations in which the hC sulfur ligates to iron, [41,47] and conformations in which the hC side chain is oriented away from the metal, which is bound instead by the carbonyl oxygen of the hCÀ V amide bond (Figure 18A).…”
Section: Substrate Analogues With Altered Steric Profilesmentioning
confidence: 99%
“…[47] Crystallisation of the IPNSÀ FeÀ AhCV complex revealed that the additional methylene group introduces considerable flexibility when this analogue binds to IPNS. The IPNSÀ FeÀ AhCV complex shows multiple occupancy of the active-site region, including binding orientations in which the hC sulfur ligates to iron, [41,47] and conformations in which the hC side chain is oriented away from the metal, which is bound instead by the carbonyl oxygen of the hCÀ V amide bond (Figure 18A). Even when the hC sulfur is bonded to the metal, the homocysteinyl carbonyl rotates towards Phe211 to take up a position similar to that seen for the corresponding carbonyl group in IPN -that is, after cyclisation -which in turn causes rotation of the valinyl isopropyl group away from its usual position, and the water ligand trans to Asp216 remains in place.…”
Section: Substrate Analogues With Altered Steric Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…X‐ray crystal structures of apo‐IPNS [9] and the enzyme:substrate complex [10] paint a detailed structural picture of the enzyme active site. Time‐resolved studies using high‐pressure oxygenation to initiate reaction within crystalline IPNS have enabled step‐by‐step elucidation of the reaction mechanism on a structural level [11,22–25], while structures of the enzyme with ACV analogues reveal a range of binding modes and the interplay between steric and electronic effects at the IPNS active site [26–32]. Seeking.…”
Section: Introductionmentioning
confidence: 99%